2001
DOI: 10.1079/pns200070
|View full text |Cite
|
Sign up to set email alerts
|

Energy balance and cancer: the role of insulin and insulin-like growth factor-I

Abstract: Recent theories propose that a Western lifestyle may increase cancer risk through alterations in the metabolism of insulin and insulin-like growth factors (IGF; McKeown-Eyssen, 1994; Giovannucci, 1995; Kaaks, 1996; Werner & LeRoith, 1996). Insulin regulates energy metabolism, and increases the bioactivity of IGF-I, by enhancing its synthesis, and by decreasing several of its binding proteins (IGFBP; IGFBP-1 and -2). Insulin and IGF-I both stimulate anabolic processes as a function of available energy and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
432
3
3

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 544 publications
(449 citation statements)
references
References 231 publications
11
432
3
3
Order By: Relevance
“…Studies have implicated obesity, lack of exercise, dietary glycemic load (an estimation of post-prandial glucose response), and diabetes mellitus as risk factors for pancreatic cancer (Gapstur et al, 2000;Michaud et al, 2001Michaud et al, , 2002Eberle et al, 2005;Huxley et al, 2005;Larsson et al, 2005). The mechanisms by which these factors increase cancer risk have been hypothesized to involve insulin and the insulin-like growth factor axis, which are intimately involved in glucose and energy homeostasis (Kaaks and Lukanova, 2001;Jerome et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have implicated obesity, lack of exercise, dietary glycemic load (an estimation of post-prandial glucose response), and diabetes mellitus as risk factors for pancreatic cancer (Gapstur et al, 2000;Michaud et al, 2001Michaud et al, , 2002Eberle et al, 2005;Huxley et al, 2005;Larsson et al, 2005). The mechanisms by which these factors increase cancer risk have been hypothesized to involve insulin and the insulin-like growth factor axis, which are intimately involved in glucose and energy homeostasis (Kaaks and Lukanova, 2001;Jerome et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…36 It has been hypothesized that the nonlinear relationship between increasing adiposity and circulating IGF-I levels is due to weight-related disruptions in insulin and GH secretion. 13,45,46 Prolonged fasting, as observed in patients with anorexia nervosa, and short-term fasting of normal-weight subjects, results in decreased IGF-I levels, 47,48 and there is a stepwise increment of IGF-I values related to weight gain in anorexic patients. 49 Short-term overfeeding of normalweight women also results in increased IGF-I levels.…”
Section: Discussionmentioning
confidence: 99%
“…Energy balance, dietary energy intake, and to a lesser extent protein intake, may be linked to cancer risk [47,48] and have been implicated in the modulation of the IGF-system. Experimental studies in animals and humans have shown that severe dietary energy and protein restriction (e.g.…”
Section: Discussionmentioning
confidence: 99%